ANALISIS KERUSAKAN JALAN AKIBAT MUATAN BERLEBIH (STUDI KASUS JALAN KABANJAHE-KUTACANE) - Parada Afkiki Eko Saputra; Almah Muddin (Universitas Quality, 2022)
The Kabanjahe-Kutacane road section is the main route connecting regencies and cities in the province of North Sumatra, as well as connecting between provinces on the island of Sumatra. This road segment is often traversed by heavy vehicles loaded with basic necessities, so there is the potential for frequent traffic violations such as vehicle loads that are more than what is permitted. This study was conducted to determine the impact of road damage that occurs if the vehicle load is excessive and to determine the value of the degree of road damage from overloaded roads and to find the remaining life (reaming life) of road pavements with excessive loads on the road. This research was conducted using data collection methods, both data from direct surveys to the location of roads or journals related to road damage, analyzed by qualitative methods which emphasize on facts on the ground and take advantage of existing theories as supporting material. The results of the analysis show that vehicle loads that have exceeded the heaviest axle load (MST) can affect the strength of the pavement layer thereby reducing the technical design life of the road from 5 years to 4,551 years. Overloading of goods transport vehicles not only reduces the design life of the road but can also cause damage to the asphalt such as potholes, crocodile cracks and distortion. From the results of the analysis, several suggestions can be given for prevention and improvement in the future, namely taking strict action against violations of goods transport vehicles that exceed the Heaviest Axis Load (MST), namely sanctions for decreasing and sanctions for not crossing roads or warnings to companies and fines to companies. directly.